DOI: 10.11606/t.3.2019.tde-16092019-144335
|View full text |Cite
|
Sign up to set email alerts
|

Concrete water footprint: a streamlined methodology

Abstract: Water is the most used substance in the world, followed by concrete. Water scarcity is nowadays more common due to concentrated population growth and climate change. Concrete demand is ~15 billion m 3 per year fulfilling the need for more and better housing and infrastructure for a growing and wealthier population. Since no other material could fulfil this demand, concrete needs to be produced in a sustainable way, minimizing environmental loads such as water consumption. The water footprint is a tool that mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…The water footprint is often used over large land areas which have been instrumental in calculating total water use in the agricultural and industrial sectors [16,17]. The framework has been applied at a smaller scale to identify water within steel and concrete production; but this has shown that there is often significant variation in the quantities of embodied water by region [18][19][20]. Research performed by Crawford, Stephan, and Prideaux has led to the creation of an extensive database of construction materials that are Australian-centered [21].…”
Section: Introductionmentioning
confidence: 99%
“…The water footprint is often used over large land areas which have been instrumental in calculating total water use in the agricultural and industrial sectors [16,17]. The framework has been applied at a smaller scale to identify water within steel and concrete production; but this has shown that there is often significant variation in the quantities of embodied water by region [18][19][20]. Research performed by Crawford, Stephan, and Prideaux has led to the creation of an extensive database of construction materials that are Australian-centered [21].…”
Section: Introductionmentioning
confidence: 99%
“…The water demand indicator is based on the indicator proposed by Mack-Vergara (2019). It represents the volume of water removed from and not immediately returned to nature with the same (or better) quality because of evaporation, incorporation into products, or release back into water bodies with lower quality (Equation 15and Figure 64).…”
Section: Water Demandmentioning
confidence: 99%